2021
DOI: 10.1016/j.jseint.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Bristow versus Latarjet in high-demand athletes with anterior shoulder instability: a prospective randomized comparison

Abstract: Background Traumatic anterior shoulder instability is a common disease, especially in young athletes. The Latarjet and Bristow techniques are nonanatomical surgeries that involve the transfer of the coracoid process to the anterior border of the glenoid and are indicated in cases at a high risk for recurrence and in the presence of associated bone lesions. Studies have evaluated the recurrence and complications associated with these techniques, but they have important differences, and should not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 21 publications
3
23
0
3
Order By: Relevance
“…assessed the ASORS scores in a prospective randomized trial with athletes and found a mean of 39 in the preoperative period and a mean of 88 at a 3-year follow-up period. 3 Their results are similar to those presented in our study, where the majority of patients had good to excellent scores, showing satisfactory results in this group of patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…assessed the ASORS scores in a prospective randomized trial with athletes and found a mean of 39 in the preoperative period and a mean of 88 at a 3-year follow-up period. 3 Their results are similar to those presented in our study, where the majority of patients had good to excellent scores, showing satisfactory results in this group of patients.…”
Section: Discussionsupporting
confidence: 89%
“…Regardless of the particularities of female athletes, after the Latarjet procedure, participants may recover their range of motion to similar results before surgery. 3 , 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…As described in the modified Latarjet technique, no coracoacromial ligament repair was made in the joint capsule. 13,14 Postsurgical Tomographic Evaluation…”
Section: Surgical Techniquementioning
confidence: 99%
“…26 No DTA studies reported nerve-related or screwrelated complications, though it is unclear whether these were explicitly assessed. For coracoid procedures, screw-related complications were reported in over a third of studies or study arms (34/84, 4.5%) and included irritation, 64 malposition, 54 bending, 87 fracture, 34 general "irregularity," 97 and loosening 37 ; these complications occurred at low rates, but some were severe enough to require revision surgery. 23 Nerve-related injury at the site of bone augmentation was reported in 16 of the 84 coracoid bone studies (19.0%); pathologies included neuropraxia, 113 nerve palsy, 51 paresthesia, 96 and transient lesion on a nerve.…”
Section: Surgical Complicationsmentioning
confidence: 99%